2019
DOI: 10.3390/fib7020017
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Strain/Damage Monitoring of Glass/Epoxy Composites with Graphene as a Piezoresistive Interphase

Abstract: Graphene as an interphase not only improves the mechanical performance of fiber reinforced polymer composites but also induces functional properties like electrical conductivity, thus providing the possibility of strain monitoring in real time. At this aim, graphene oxide (GO) was electrophoretically deposited at different applied potentials on glass fibers to create a uniform coating and was subsequently chemically reduced to obtain a conductive layer of reduced graphene oxide (rGO). After the optimization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…The PEDOT:PSS/PU substrates indicated a sheet resistance of 35–240 Ω/sq, withstand a strain of 200% and showed a constant resistance after 10 stretch release cycles [37]. Mahmood et al, showed the manufacture of conductive graphene oxide glass fiber substrates, which impart an electrical resistivity of 10 1 Ωm after electrophoretical deposition [38]. In the review, Ding et al reported on the conductive sponges as pressure sensors like neat conductive sponges (e.g., impregnated with Cu nanowires, CNT), composite conductive sponges (e.g., composed of polyimide (PU), polyacrylonitrile (PAN)), conductive sponges impregnated with elastomers (e.g., silicone, polydimethylsiloxane (PDMS)) and like conductive material coated sponges (e.g., coated with carbon, Ag).…”
Section: Introductionmentioning
confidence: 99%
“…The PEDOT:PSS/PU substrates indicated a sheet resistance of 35–240 Ω/sq, withstand a strain of 200% and showed a constant resistance after 10 stretch release cycles [37]. Mahmood et al, showed the manufacture of conductive graphene oxide glass fiber substrates, which impart an electrical resistivity of 10 1 Ωm after electrophoretical deposition [38]. In the review, Ding et al reported on the conductive sponges as pressure sensors like neat conductive sponges (e.g., impregnated with Cu nanowires, CNT), composite conductive sponges (e.g., composed of polyimide (PU), polyacrylonitrile (PAN)), conductive sponges impregnated with elastomers (e.g., silicone, polydimethylsiloxane (PDMS)) and like conductive material coated sponges (e.g., coated with carbon, Ag).…”
Section: Introductionmentioning
confidence: 99%
“…Methods for tracking damage evolution in real-time during an experiment are being developed. Mahmood et al coated glass fibres with graphene oxide (which is piezoresistive) in order to record strain in real time [295] -with the added benefit that the graphene oxide layer improved the flexural strength by 23% and the interlaminar shear strength by 29%. Minnaar developed a non-contact crack detection method [290] which consisted of a series of four laser interferometers that measured the displacements of the surface, allowing the degree of delamination to be determined.…”
Section: Damage Failure and Energymentioning
confidence: 99%
“…Epoxy based blends and composites have been actively researched in the past century not only for structural applications, but also for smart multifunctional materials. [1][2][3][4][5] For almost a couple of decades, scientists and researchers around the world have been pursuing with great interest the development of self-healable polymer and composites. [6][7][8][9][10][11] The first work reported by White et al 12 in this field involved the use of extrinsic elements in the bulk polymer, that is, capsules and a catalyst for the self-healing of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy based blends and composites have been actively researched in the past century not only for structural applications, but also for smart multifunctional materials 1–5 . For almost a couple of decades, scientists and researchers around the world have been pursuing with great interest the development of self‐healable polymer and composites 6–11 .…”
Section: Introductionmentioning
confidence: 99%